Post-Surgical Pneumoperitoneum Comparison of Abdominal Ultrasound Findings and Plain Radiography - elfseie , Arwi barka elfseie; BenGeweref, Nadya; Muftah, Kamla; buagrara, Muftah; Nowara. A. Ahmed Elsharif; Abdelhakim Algheryani (AlQalam Journal of Medical and Applied Sciences, 2025)
Pneumoperitoneum refers to the presence of air within the peritoneal cavity and can be divided into two subgroups: surgical pneumoperitoneum (90%) and nonsurgical pneumoperitoneum (10%). Postoperative pneumoperitoneum, a benign and self-limited finding, takes up to 24 days after surgery to resolve. Generally, it resolves within 3-6 days. To determine the sensitivity of ultrasound (USS) in detecting post-surgical pneumoperitoneum and to compare abdominal ultrasonography findings with plain radiography (X-ray), this study is a cross-sectional study carried out at the Radiology Department of Benghazi Medical Center from January 2018 to December 2018. The study included 90 patients aged 15 to 80 years, with a mean age of 37 ± 17.2 years. The types of surgery were as follows: Cholecystectomy (32.2%), Appendectomy (25.7%), Inguinal hernia repair (11%), Segmental sigmoidectomy (5.6%), and Diagnostic laparoscopy (10%). Left hemicolectomy, Splenectomy, ovarian cyst removal, and incisional hernia repair accounted for 2.2% each. Para-umbilical hernia, Hiatus hernia, Colon cancer resection, Sigmoidectomy, choledochoduodenostomy, and umbilical hernia repair accounted for 1.1% each. The timing of X-rays showed that 88.9% were done at the same time as USS and 11.1% were performed 24 hours after USS. Post-surgical pneumoperitoneum was present in 98.6% of cases on USS and X-ray. 12.1% of males and 17.5% of females. The difference was not statistically significant (p-value = 0.494). The study concluded that the sensitivity of USS was superior to abdominal radiography in the diagnosis of pneumoperitoneum.